Review Deskriptif Antacedent Knowledge Sharing - Aqilla Tauhidta Arla Putri; Syamsul Hadi; Aulia Rosiana (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Objectives - This article focuses on the cognitive and cultural closeness between employees where both can imply knowledge sharing well so as to develop a competitive organization. Method - This article uses a descriptive review method. Descriptive review is research obtained from scientific articles from PERPUSNAS sources (RI national library). Findings- Knowledge sharing has been carried out by many researchers (empirical studies) by researchers around the world. However, no one has yet conducted a descriptive review focusing on the turbulence of the COVID-19 pandemic which has impacted almost all business processes. Keywords: empirical study, knowledge sharing